VISUALISASI KATA KUNCI PEMBERITAAN PEMILU 2024 MENGGUNAKAN SCAPY DAN WORDCLOUD - Arif Chandra, M. Iqbal; Yusuf, Ridwan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
In the digital information age, understanding relevant keywords in internet search results has become increasingly important. This article discusses the analysis of keywords from Google Custom Search results using the text processing tool Spacy and the WordCloud visualization technique. This method allows for more effective processing and presentation of keywords, assisting users in understanding the essence of various search queries. The experimental results demonstrate that this approach can reveal the most significant keywords in search results, helping users identify trends and focus on topics that appear in their searches. Thus, this article provides insights into enhancing the understanding of keywords in internet search results with the assistance of powerful text processing and visualization tools.